Functional haplotypes in interleukin 4 gene associated with periodontitis - Anovazzi, Giovana [UNESP]; De Medeiros, Marcell Costa [UNESP]; Pigossi, Suzane Cristina [UNESP]; Finoti, Livia Sertori [UNESP]; Mayer, Marcia Pinto Alves; Rossa, Carlos [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP] (Public Library of Science (PLoS), 2017)
Chronic periodontitis (CP) is an infectious inflammatory disease that affects tooth-supporting structures and in which dental plaque bacteria, immune mechanisms and genetic predisposition play important roles. Interleukin 4 (IL-4) is a key anti-inflammatory cytokine with relevant action in imbalances in inflamed periodontal tissue. Individuals carrying the TCI/CCI genotype (S-haplotype) of the IL-4 gene are 5 times more susceptible to CP, whereas the CTI/TTD genotype (P-haplotype) confers protection against CP. Compared with the Shaplotype, subjects with the P-haplotype produce higher levels of the IL-4 protein after non-surgical periodontal therapy. The present in vitro study aimed to investigate the functionality of IL-4 haplotypes in immune cells to obtain insight into the influence of these genetic variations in regulating immune responses to CP-associated bacteria. Peripheral blood was collected from 6 subjects carrying each haplotype, and their immune cells were challenged with periodontopathogens to compare responses of the different haplotypes with regard to gene expression, protein secretion and the immunophenotype of T helper responses. We found higher IL-4 mRNA and protein levels in the P-haplotype, which also presented higher levels of anti-inflammatory cytokines. In contrast, cells from S-haplotype subjects responded with higher levels of pro-inflammatory cytokines. S-haplotype individuals exhibited significantly greater polarization toward the Th1 phenotype, whereas the Phaplotype was associated with an attenuated response to periodontopathogens, with suggestive skewing toward Th2/M2 phenotypes. In conclusion, IL-4 genetic variations associated with susceptibility to or protection against chronic periodontitis are directly associated with influencing the response of immune cells to periodontopathogens.